3D steerable, acoustically powered microswimmers for single-particle manipulation - Ren, Liqiang; Nama, Nitesh; McNeill, Jeffrey M.; Soto, Fernando; Yan, Zhifei; Liu, Wu; Wang, Wei; Wang, Joseph; Mallouk, Thomas E. (Science advances, 2019)
Trapped bubbles make for fast and controllable microswimmers that can push or pull living cells in crowded microenvironments. The ability to precisely maneuver micro/nano objects in fluids in a contactless, biocompatible manner can enable innovative technologies and may have far-reaching impact in fields such as biology, chemical engineering, and nanotechnology. Here, we report a design for acoustically powered bubble-based microswimmers that are capable of autonomous motion in three dimensions and selectively transporting individual synthetic colloids and mammalian cells in a crowded group without labeling, surface modification, or effect on nearby objects. In contrast to previously reported microswimmers, their motion does not require operation at acoustic pressure nodes, enabling propulsion at low power and far from an ultrasonic transducer. In a megahertz acoustic field, the microswimmers are subject to two predominant forces: the secondary Bjerknes force and a locally generated acoustic streaming propulsive force. The combination of these two forces enables the microswimmers to independently swim on three dimensional boundaries or in free space under magnetical steering.